TO THE MATTER OF ACCOUNTING OF NON-UNIFORMITY OF HEAT OF SUPERHEAT OUTLET IN CRYSTALLIZER AT CONTINUOUS CASTING - E. B. Demchenko; E. I. Marukovich (Литьë и металлургия)
It is offered to tale into account irregular character of the heat of superheat allocation in liquid cup of casting by criterion of nonuniformity of the heat of superheat discharge along perimeter of the solidification front.